β-Glucosidase production by Trichoderma reesei and Thermoascus aurantiacus by solid state cultivation and application of enzymatic cocktail for saccharification of sugarcane bagasse - Frassatto, Priscila Aparecida Casciatori [UNESP]; Casciatori, Fernanda Perpétua; Thoméo, João Cláudio [UNESP]; Gomes, Eleni [UNESP]; Boscolo, Maurício [UNESP]; da Silva, Roberto [UNESP] (Springer Nature, 2020)
For degradation of sugarcane bagasse (SCB), several enzymes are needed but β-glucosidase is rate limiting in cellulose hydrolysis. Since different microorganisms synthetize characteristic pool of enzymes, mixing extracts produced by different species may increase hydrolytic efficiency due to synergism between enzymes in cocktails. This paper reports the study of β-glucosidase production in solid state cultivation (SSC) of two filamentous fungi, thermophilic Thermoascus aurantiacus and mesophilic Trichoderma reesei, and application of the enzymatic extracts on non-pretreated SCB saccharification. Enzyme extract obtained from the thermophilic fungus presented higher β-glucosidase and FPU activities (1.8 U/mL and 10 FPU/mL) than the one from mesophilic (0.2 U/mL and 6 FPU/mL). Optimal SCB hydrolysis was achieved when applying enzymatic cocktail composed of equal volumes of both fungal extracts (3.6 FPU/gSCB, filter paper units per gram SCB, 2.25 FPU/gSCB provided by extract from T. aurantiacus and 1.35 FPU/gSCB from T. reesei) at 65 °C. The hydrolysis yield applying the enzyme cocktail, 124 mg total reducing sugars (TRS) per gSCB, was higher than any yield achieved when using the enzyme extracts separately (105 mgTRS/gSCB using 12.5 FPU per gSCB from T. aurantiacus at 65 °C; 79 mgTRS/gSCB using 7.5 FPU per gSCB from T. reesei at 45 °C). Therefore, the use of the cocktail (3.6 FPU/gSCB) at 65 °C released 18 and 57% more TRS respectively than when extracts from T. aurantiacus or from T. reesei were applied alone, respectively, even reducing enzyme load (FPU) by 70%, corroborating the synergistic effect when both extracts are used together.
Keywords: Biofuels; Enzymes; Fermentation biotechnology; Fungal growth; Hydrolysis